2021
DOI: 10.1007/s40670-021-01382-z
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Delivering Cross-Cultural Medical Education in the UK and Malaysia

Abstract: Newcastle University UK operates an international campus, NUMed, in Malaysia. NUMed delivers the same medical degree programme as in the UK, within a different cultural context. In this paper, medical education faculty and NUMed graduates with experience working in both the UK and Malaysia provide insights into cross-cultural diversity in approaches to learning. Observations from small and large group teaching and approaches to assessment are discussed in relation to students’ cultural backgrounds including pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 84 publications
0
7
0
Order By: Relevance
“…Although Newcastle students noted the efficiency of the Malaysian healthcare system in terms of numbers of patients treated in reduced time, the trade-off was doctor led care drawing from a paternalistic healthcare system 34. The more paternalistic approach could be driven by patient preference and cultural factors, with poorer patients and less well-educated patients preferring the paternalistic approach 28 34. For example, the older generation and those less well educated may be more familiar with a paternalistic approach and prefer doctors to make the decisions for them, believing this is the doctor’s role and feeling they are not qualified to take on this shared responsibility 34 35…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although Newcastle students noted the efficiency of the Malaysian healthcare system in terms of numbers of patients treated in reduced time, the trade-off was doctor led care drawing from a paternalistic healthcare system 34. The more paternalistic approach could be driven by patient preference and cultural factors, with poorer patients and less well-educated patients preferring the paternalistic approach 28 34. For example, the older generation and those less well educated may be more familiar with a paternalistic approach and prefer doctors to make the decisions for them, believing this is the doctor’s role and feeling they are not qualified to take on this shared responsibility 34 35…”
Section: Discussionmentioning
confidence: 99%
“…This is further highlighted by Azila et al who conducted a study with Malaysian students who reported finding PBL challenging,43 an issue also highlighted by NUMed students when starting at Newcastle. However, interestingly both sets of students adapted to the new approach at each campus and saw the value of a different approach to teaching and learning 28 38…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations